Changes in the palliative performance scale may be as important as the initial palliative performance scale for predicting survival in terminal cancer patients. Issue 5 (October 2021) - Lee, Guk Jin; Gwak, Ji Hyun; Kim, Myoung Sim; Lee, Mi Yeong; Kim, Seo Ree; Chun, Sang Hoon; Jin, Jong Youl
Abstract: Objective: The accurate estimation of expected survival in terminal cancer patients is important. The palliative performance scale (PPS) is an important factor in predicting survival of hospice patients. The purpose of this study was to examine how initial status of PPS and changes in PPS affect the survival of hospice patients in Korea. Method: We retrospectively examined 315 patients who were admitted to our hospice unit between January 2017 and December 2018. The patients were divided based on the PPS of ≥50% (group A) and ≤40% (group B). We performed survival analysis for factors associated with the length of survival (LOS) in group A. Based on the hospice team's weekly evaluation of PPS, we examined the effect of initial levels and changes in group A on the prognosis of patients who survived for 2 weeks or more. Results: At the time of admission to hospice, 265 (84.1%) patients were PPS ≥50%, and 50 (15.9%) were PPS ≤40%. The median LOS of PPS ≥50% and PPS ≤40% were 15 (2–158 days) and 9 (2–43 days), respectively. Male, gastrointestinal cancer, and lower initial PPS all predicted poor prognosis in group A. Male, gastrointestinal cancer, and a PPS change of 10% or greater, compared with initial status 1 week and 2 weeks of hospitalization, were all predictors of poor prognosis in group A patients who survived for 2 weeks or longer. Significance of results: Our research demonstrates the significance of PPS change at 1 week and 2 weeks, suggesting the importance of evaluating not only initial PPS but also change in PPS.